Keeper - Appelt, Kathi, 1954- (Atheneum Books for Young Readers, 2012)
On the night of the blue moon when mermaids are said to gather on a sandbar in the Gulf of Mexico, ten-year-old Keeper sets out in a small boat, with her dog BD and a seagull named Captain, determined to find her mother, a mermaid, as Keeper has always believed, who left long ago to return to the sea.